#1)______________________________________
√(x^4x^3)
First, seperate into two "Square Roots".
√(x^4) √(x^3)
The root of a "Square Root" is the #2.
So to ELIMINATE the ²√ , we need to raise the INSIDE to the "Power" of 2 . . . ( )².
When the Root and the Power are the SAME. . . the INSIDE (known as The Descriminant) comes out.
But the Root and the Power MUST BE THE SAME!
Whatever is leftover is the REMAINDER under the "Square Root".
²√(x²)² ²√(x¹)² ²√(x¹)
(x²)(x¹)√(x¹)
When Multiplying w/ "like bases" (variables). . . ADD the exponents together.
(x ² + ¹)√(x)
ANSWER #1=================================
√(x^4x^3) = (x³)√(x)
==============================================
#2)_______________________________________________
[8√(5)] - √(20)
[8√(5)] - [√(4)√(5)]
[8√(5)] - [2√(5)]
ANSWER #2 =====================================
[8√(5)] - √(20) = 6√(5)
==============================================
#3)______________________________________________
{ [ √(20) ] / 5 } - [ 1/√(5) ]
{ [ √(20) ] / 5 } - { [1][√(5)] / [√(5)][√(5)] }
{ [ √(20) ] / 5 } - { [√(5)] / 5 }
{ [√(4)√(5)] / 5 } - { [√(5)] / 5 }
{ [2√(5)] / 5 } - { [1√(5)] / 5 }
{ [2√(5)] - [1√(5)] } / 5
[1√(5)] / 5
ANSWER #3 =================================
{ [ √(20) ] / 5 } - [ 1/√(5) ] = [√(5)] / 5
===========================================
Good Job making it to the end with me!
Great questions!
Good luck on your Finals! ♥
^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
Additional Details
9 minutes ago
The answer to (sqrtx^4y^3) is:
x^2ysqrty or as I like to write it:
√(x^4y^3) = x²y√(y)
GOOD JOB! ♥
^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
2007-01-18 18:41:59
·
answer #1
·
answered by LovesMath 3
·
0⤊
0⤋
sqrtx^4y^3: sqrt is the same as (1/2) so you can multiply the exponents (1/2*4) and you get x^2y^3
(8sqrt5)-(sqrt20): square roots of large numbers can be broken down into multiples of those numbers. sqrt20 can be broken down into sqrt5*sqrt4 sqrt4=2 and the problem becomes (8sqrt5)-(2sqrt5)=6sqrt5
sqrt20/5-1/sqrt5: multiply the 1/sqrt5 by sqrt5 to get 1sqrt5/5 you now have a common denominator of 5. replace the sqrt20 with 2sqrt5(see above) and the equation becomes 2sqrt5/5-1sqrt5/5=1sqrt5/5
2007-01-18 18:22:37
·
answer #2
·
answered by Ben B 4
·
0⤊
0⤋
okay, lets see.. all you do is remember that "sqrt" is the same as "to the exponent 1/2) so the first one..
(x^4*y^3)^(1/2) then use your law of exponents (multiplying one)..
= x^2*y^(3/2) = x^2*sqrt(y^3)
next, is 8sqrt(5) - sqrt(20) now, the only way you can add/subract terms with radicals if they have the same radical. knowing this.. sqrt(20) can be broken up into sqrt(4)*sqrt(5) which = 2sqrt(5)
so 8sqrt(5) - 2sqrt(5) = 6sqrt(5)
last question! again, you can simplify sqrt(20) into 2sqrt(5) so..
2sqrt(5)/(5) - 1/(sqrt(5))... to add/subtract fractions, you need a common denominator.. so we multiply the second term by sqrt(5)/sqrt(5) [which is the same as 1, so we're not changing it..] and we get..
2sqrt(5)/(5) - sqrt(5)/(5)
= sqrt(5)/(5) = (5)^(-1/2) = 1/(sqrt(5))
but generally, we keep the "demoninator rationalized" so the it's sqrt(5)/(5)
working with squareroots, or any radicals for that matter is basically just working with exponents. Just make sure you study those law of exponents and you'll be fine!
2007-01-18 18:24:01
·
answer #3
·
answered by BananaPancakes 2
·
0⤊
1⤋
If everything is multiplied or divided together under the radical with no addition or subtraction, whatever you collect in squares can be taken out. For example x^7 = (x³)(x³)x so x³ can be taken out of the radical and x is left behind under the radical.
√(x^4y^3) = √{(x²)²(y²)y} = x²y√y
(√20)/5 - 1/√5 = (2√5)/5 - (√5)/5 = (√5)/5
2007-01-18 18:15:17
·
answer #4
·
answered by Northstar 7
·
1⤊
0⤋
1/ sqrt(x^4y^3) = (x^2)(y)(sqrt y)
2/ (8sqrt5) - (sqrt20) = (8sqrt5) - {sqrt(4x5)} = (8sqrt5) - (2sqrt5) = 6sqrt5
3/ {(sqrt20)/5} - {1/(sqrt5)
first simplify (sqrt20)/5 = {sqrt (4x5)}/5 = {2(sqrt5)}/5 = 2/ (sqrt5)
Now take the one you simplify minus the second part because they have the same common denominator now.
{2/(sqrt5)} - {1/(sqrt5)} = 1/(sqrt5) = (sqrt5)/5
never leave the square root as the answer for the denominator.
2007-01-18 18:26:46
·
answer #5
·
answered by chembiomajor 1
·
1⤊
0⤋
one way is to right component the quantity, and write out the variable, and then for each pair of equivalent aspects, positioned one among them outdoors the ? (and remove the different). Like for yours, you'll have ?3•3•3•a•a one pair of three's and one pair of a's, with a three left over so 3a?3 also, for a classic sq. root, you'll locate the biggest perfect sq. component of it, write the quantity as a multiply project using that component, then separate into 2 sq. roots and simplify your sq. root of the perfect sq.. As in: ?seventy 2 = ?36•2 = ?36•?2 = 6?2 ?27 = ?9•3 = ?9?3 = 3?3
2016-10-15 10:46:19
·
answer #6
·
answered by serpa 4
·
0⤊
0⤋
Answers:
1)sqrtx^4y^3 = sqrt ( x^(64y^3))
= x ^ (64y^3/2)
= x^ (32y^3)
2) (8sqrt5) - (sqrt20) = (8sqrt5) - sqrt(4*5)
= 8sqrt5 - 2sqrt5 = 6 sqrt (5)
3) sqrt20 1 2 sqrt 5 1
-------- - ------- = -------------- - ---------
5 sqrt5 sqrt 5 *sqrt 5 sqrt 5
2 1
= -------- - --------
sqrt 5 sqrt 5
= 1 / (sqrt 5)
2007-01-18 18:48:46
·
answer #7
·
answered by Poornima G 2
·
0⤊
1⤋
1*
so the problem is 8(5)^(1/2) - (20)^(1/2)
to simplify these equations, you need to try to make
8(5)^(1/2) - (20)^(1/2)
....^........and..^....values the same
in this case 20 = 2^(2)*5
8(5)^(1/2) - (2^(2)*5)^(1/2)
take 2 out of the root
8(5)^(1/2) - 2(5)^(1/2)
now just subtract it and you get
6(5)^(1/2)
2*
[(20)^(1/2) / 5] - [1 / (5)^(1/2)]
the (20)^(1/2) = 2(5)^(1/2) shown on the top
and 5 = [5^(1/2)]^2
so
2(5)^(1/2) / [5^(1/2)]^2 = [(20)^(1/2) / 5]
= 2 / (5)^(1/2)
back to the equation
2 / (5)^(1/2) - 1 / (5)^(1/2)
which is
1 / (5)^(1/2)
2007-01-18 18:23:07
·
answer #8
·
answered by Taras 2
·
0⤊
1⤋
1.
z=sqrt (x^4y^3)
=sqrt(x^4*y^3)
=sqrt(x^4)*sqrt(y^3)
=x^2sqrt(y^3)
2.
z = 8sqrt(5) - sqrt(20)
= 8sqrt(5) - sqrt(4*5)
= 8sqrt(5) - 2sqrt(5)
= 6sqrt(5)
3.
z = sqrt(20) - 1
---------- ----
5 sqrt(5)
z = 20^(1/2) - 1
---------- ----
5 5^(1/2)
z = 20^(1/2) - 5^(-1/2)
----------
5
z = 20^(1/2) - 5^1 * 5^(-1/2)
------------------------------
5
z = 20^(1/2) - 5^(1/2)
----------------------
5
z = sqrt(20) - sqrt(5)
----------------------
5
z = sqrt(4*5) - sqrt(5)
----------------------
5
z = 2sqrt(5) - sqrt(5)
----------------------
5
z =sqrt(5)
--------
5
2007-01-18 18:33:58
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋